(untitled) (Pubmet, 2022)
Oxford University Press (OUP) is the world’s largest university press, with the widest global presence. This makes us uniquely placed to increase your impact, by connecting your ideas and research to a diverse readership. Our mission is to further the University of Oxford’s objective of excellence in research, scholarship, and education, by publishing worldwide. This mission guides how we work with the academic community and the content we produce. For over 500 years, OUP has published the world’s finest minds, shaping and developing important and rigorous research and scholarship. As an OUP author, you are part of a prestigious tradition of excellence. When you publish with OUP, you benefit from our: ▸ reputation for quality, ▸ long term publishing experience coupled with future facing innovation and investment, ▸ global presence and reach, connecting your work with diverse readers and maximizing your impact, ▸ trusted relationships with the academic community. Our dedicated and expert publishing teams support you every step of the way, adding value through constructive collaboration and helpful intervention to help your work reach its full potential. We connect powerful ideas with the widest audience, so that your research and scholarship achieve the greatest possible impact. We know, that publication represents the culmination of years of hard work, dedication, and passion. We are future-facing and always innovating, keeping our eye on what is coming next for our community and how we can facilitate better research outcomes. We invest and innovate to help improve the scholarly communications landscape for both authors and readers, and to make sure that our content is available in a way that meets the changing needs of scholars and researchers. Quality is the main criterion we consider when evaluating a new title for publication. All our publications are peer-reviewed by outside readers or our editorial staff, to ensure we maintain the highest standards of scholarship and research. OUP is committed to supporting different business models in the dissemination of our scholarly research and has read and publish agreements with institutions and consortia worldwide. We believe in the power of research to make a better tomorrow, and so we invite you to partner with OUP to help your work reach its full potential and reach readers across the world.